Socio-economic inequality in mortality and healthcare utilization: Evidence from cancer patients - Wolfgang Frimmel; Felix Glaser (Johannes Kepler University of Linz, Department of Economics, 2024)
Health equality is an important objective in public healthcare systems, and still, we see substantial socio-economic differences. Using high-quality administrative data from Upper Austria, we analyze the socio-economic gradient in mortality and healthcare utilization following a cancer diagnosis. High-SES patients are less likely to die after a cancer hospitalization even when accounting for a comprehensive set of controls, including detailed pre-shock healthcare use. After hospital discharge, patients navigate the healthcare system differently depending on their socio-economic status. We explore potential explanations for the observed SES gradient. Our findings suggest that low-SES cancer patients go to the hospital at a later stage of the disease. Peer groups also matter in explaining SES differences, while healthcare providers do not appear to contribute significantly to the gap. Targeted policies that take into account disease heterogeneity, health awareness, and prevention behavior have the potential to reduce health inequalities.
Keywords: I14; I12; 330; Health Inequality; SES; Mortality; Health Behavior; Cancer